2023
DOI: 10.1007/s00521-023-08285-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of machine learning techniques for stance detection and its applications

Abstract: Stance detection is an evolving opinion mining research area motivated by the vast increase in the variety and volume of user-generated content. In this regard, considerable research has been recently carried out in the area of stance detection. In this study, we review the different techniques proposed in the literature for stance detection as well as other applications such as rumor veracity detection. Particularly, we conducted a systematic literature review of empirical research on the machine learning (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 140 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…However, despite the benefits of sentiment and the recent research into computational tools for sentiment classification, sentiment alone has limited utility in understanding more contextual attitudes and opinions, like stance. Stance detection entails the automated prediction of an author's viewpoint or stance towards a subject of interest, often referred to as the "target" [31]. Typically, a stance towards a subject is categorized as "Agree", "Disagree", or "Neutral".…”
Section: Natural Language Understanding and Media Biasmentioning
confidence: 99%
“…However, despite the benefits of sentiment and the recent research into computational tools for sentiment classification, sentiment alone has limited utility in understanding more contextual attitudes and opinions, like stance. Stance detection entails the automated prediction of an author's viewpoint or stance towards a subject of interest, often referred to as the "target" [31]. Typically, a stance towards a subject is categorized as "Agree", "Disagree", or "Neutral".…”
Section: Natural Language Understanding and Media Biasmentioning
confidence: 99%
“…According to the identified gap in a recent Systematic Literature Review on stance detection by [2], further exploration is required in the field to investigate the potential of developing a joint neural architecture based on the MTL paradigm. In addition, hypotheses regarding the interaction between sentiment and stance appear to be debatable.…”
Section: Legalization Of Abortionmentioning
confidence: 99%
“…Despite its recent emergence, there has been a noteworthy endeavor to construct models specifically tailored for tackling stance detection [2]. Past studies on stance detection utilized feature engineering with a support vector machine (SVM) classifier [15,[20][21][22][23], gradient boosting [24], and k-nearest neighbors (KNN) [25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review performed in 2019 on existing opinion mining approaches using data from social media platforms found that 94% of the 461 included studies use data only from one social media platform and the vast majority of the studies used data from X (formerly known as Twitter), followed by Sina Weibo and Facebook [12]. Furthermore, in another systematic review of techniques for stance detection published in 2023 [13], social media was the data source of 72% of the 96 included articles in the study.…”
Section: Introductionmentioning
confidence: 99%